Definition and assessment of physical efficiency of students – basketball players - Кузьминчук, Артем Петрович; Градусов, Володимир Олексійович (Slobozhanskyi Herald of Science and Sport, 2016)
Kuzminchuk A., Gradusov V. Purpose: assess the level of physical efficiency of students – basketball players by using the Harvard step test. Material & Methods: the analysis of scientific-methodical literature, educational testing, pedagogical experiment, methods of mathematical statistics. For determination and assessment physical efficiency of students – basketball players used the Harvard step test. In pedagogical testing for assessing special performance was attended by 14 students – basketball players (n=14) men's teams of the Medical Institute of Sumy State University. Results: the analysis of scientific and technical literature showed gaps in training basketball players, namely, to improve the physical performance. Especially these problems are when basketball training sessions combine with study in higher educational institutions. The load that caused a combination of mental and physical labor is enough to affect on the performance, develop resistance to fatigue. Still need to look for approaches that can help in conditions of single 3-4 workouts per week to maintain a high level of physical capacity of basketball players. Conclusions: analyzing the test results of basketball team players at Medical Institute of Sumy State University, we can say that the level of physical performance is satisfactory and functional status is mediocre. Players need more regular training which includes special exercises with high intensity close to competitive conditions.